Structure and dynamics of convective mixing in Lake Onego under ice-covered conditions. Issue 2 (3rd April 2019) - Bogdanov, Sergey; Zdorovennova, Galina; Volkov, Sergey; Zdorovennov, Roman; Palshin, Nikolai; Efremova, Tatyana; Terzhevik, Arkady; Bouffard, Damien
ABSTRACT: Hydrophysical studies conducted in Petrozavodsk Bay of Lake Onego under ice-covered conditions in March 2016 and 2017 detected radiatively driven convection and revealed specific structural and dynamic parameters for the convectively mixed layer (CML). Analysis of time series, spectral energy distribution, and vertical velocity profiles indicated the presence of a mean current, seiches, and convective motion. Because of their similar spatial and temporal scales, these processes were investigated using progressive-vector diagrams (PVDs). Despite low water velocities, the CML hydrodynamic regime remained close to that of fully developed turbulence, and convective cells at a range of different scales were expected. Signal resolution constraints limited detection to only the largest cells. We investigated the horizontal structure of the CML using individual and combined observations from 3 acoustic velocity profilers located within a radius of a few tens of meters. This novel setup collected data indicating that the CML's large-scale horizontal flow structure consists of a continuum of quasi-deterministic cells. Cell parameters necessary for estimating turbulent transfer were derived from PVD and hodograph curves.